2009
DOI: 10.1111/j.1365-2559.2009.03468.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of nuclear PTEN expression in colorectal adenocarcinoma

Abstract: Nuclear PTEN expression gradually decrease during the normal-adenoma-adenocarcinoma-metastasis sequence, which suggests an important role for PTEN in carcinogenesis. Moreover, loss of nuclear PTEN expression was a marker of poor clinical outcome in patients with stage II colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 38 publications
(103 reference statements)
7
58
2
1
Order By: Relevance
“…31,48 Previous studies have shown that loss of PTEN nuclear expression and BRAF mutations were associated with poor clinical outcome while the prognostic significance of PIK3CA and KRAS mutations in colorectal cancer remains elusive. 24,[49][50][51][52][53][54][55][56][57][58] In our series, loss of PTEN nuclear expression in primary tumors and the PIK3CA mutations in metastases were associated with shorter overall survival (Supplementary Table S2); however, neither PTEN expression nor PIK3CA mutations were emerged as independent prognostic factors in multivariate analysis ( Table 4). Activation of RAS/PI3K signaling network by mutation of at least one of the BRAF, KRAS and PI3KCA was associated with shorter survival, as previously reported by Barault et al (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,48 Previous studies have shown that loss of PTEN nuclear expression and BRAF mutations were associated with poor clinical outcome while the prognostic significance of PIK3CA and KRAS mutations in colorectal cancer remains elusive. 24,[49][50][51][52][53][54][55][56][57][58] In our series, loss of PTEN nuclear expression in primary tumors and the PIK3CA mutations in metastases were associated with shorter overall survival (Supplementary Table S2); however, neither PTEN expression nor PIK3CA mutations were emerged as independent prognostic factors in multivariate analysis ( Table 4). Activation of RAS/PI3K signaling network by mutation of at least one of the BRAF, KRAS and PI3KCA was associated with shorter survival, as previously reported by Barault et al (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Intensity of immunoreactivity for both antibodies was determined as 0, negative; 1, weak; 2, moderate; and 3, strong. As regards the interpretation of PTEN cytoplasmic expression, one, two or three additional points were attributed if the percentage of positive cells was o25%, 25-50% or450%; tumors with a score o4 were considered to have loss of PTEN cytoplasmic expression.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…[16][17][18] and less than 5% microsatellite stable (MSS) tumors (19,20). However, associations with advanced tumor stage and poor outcome are less certain (11,(21)(22)(23)(24). PIK3CA mutations have been reported to be more frequent in women (8,25,26), proximal (26), welldifferentiated (5), and mucinous tumors (5), but these findings have not been consistent (4,8,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…PTEN, which is located at human chromosome 10q23, has been identified as a tumor suppressor gene and an important negative regulator of the PI3K-AKT-mTOR signaling pathway that promotes cell proliferation and inhibits apoptosis (31). Inactivation of PTEN by mutation, deletion and promoter hypermethylation has been demonstrated in a range of cancer types, including lung, breast, prostate and esophageal carcinomas (31-35).…”
Section: Discussionmentioning
confidence: 99%